Nanofibrillated Cellulose Surface Modification: A Review - Julien Bras (Materials, 2013)
Interest in nanofibrillated cellulose (NFC) has increased notably over recent decades. This bio-based nanomaterial has been used essentially in bionanocomposites or in paper thanks to its high mechanical reinforcement ability or barrier property respectively. Its nano-scale dimensions and its capacity to form a strong entangled nanoporous network have encouraged the emergence of new high-value applications. It is worth noting that chemical surface modification of this material can be a key factor to achieve a better compatibility with matrices. In order to increase the compatibility in different matrices or to add new functions, surface chemical modification of NFC appears to be the prior choice to conserve its intrinsic nanofibre properties. In this review, the authors have proposed for the first time an overview of all chemical grafting strategies used to date on nanofibrillated cellulose with focus on surface modification such as physical adsorption, molecular grafting or polymer grafting.